RANCANG BANGUN MESIN UNSTRIPPED BUNCH (USB) CRUSHER DENGAN VALUE ENGINEERING - Dedi Dermawan; Japri Lukman; Hendri Ali Ardi (Jurnal Teknik Industri Terintegrasi, 2021)
Abstract PKS PT. XXX produces Â± 49,645 tons of empty fruit bunches, which is an average of 16.16% (Dok Sam 2019) of TBS processed for a year. This is less effective and there are still Unstripped Bunch (USB) which are attached to the garden area where the Empty away application is applied. From the results of the study to overcome the problem of loose loose bunches that are still in empty bunches, the Unstripped Bunch Machine (USB) Crusher unit is designed with specifications that have been adjusted and the design is made sturdy and will be directly applied in real form using the Value Engineering method, the results The reality of this machine unit is that it can reduce the loose losses in empty bunches and can reduce operator performance. The stages used in this method are the information stage, the creativity stage, the analysis stage (analysis of creative ideas, raw material costs, anthropometry, and raw material analysis). Keywords: Anthropometry, unit design, Unstripped Bunch, value engineering